Specyfika nazewnictwa Pojezierza Wałeckiego jako konsekwencja dziejów terenu - Rutkiewicz-Hanczewska, Małgorzata (Slavia Occidentalis, 2014)
The subject of the article is characteristics of the contemporary toponyms of Wałcz Lake District. Their distinctive feature is variance and well-developed synonymy (especially with reference to the names of waterrelated bodies), stemming from the broken continuity of names, restored after World War II.